USP7 sustains an active epigenetic program via stabilizing MLL2 and WDR5 in diffuse large B‐cell lymphoma. (12th April 2022) - Wu, Yuanyuan; Gu, Hongyan; Bao, Yuhua; Lin, Ting; Wang, Zhenyu; Gu, Donghua; Shen, Haoliang; Xian, Hua; Fan, Yihui; Mao, Renfang
Abstract: Activated B‐cell‐like (ABC)‐diffuse large B‐cell lymphoma (ABC‐DLBCL) is a common subtype of non‐Hodgkin's lymphoma with poor prognosis. The survival of ABC‐DLBCL relies on constitutive activation of BCR signaling, but the underlying molecular mechanism is not fully addressed. By mining The Cancer Genome Atlas database, we found that the expression of ubiquitin‐specific protease 7 (USP7) is significantly elevated in three cancer types including DLBCL. Interestingly, unlike germinal center B‐cell‐like (GCB)‐DLBCL, ABC‐DLBCL shows upregulated expression of USP7. Inhibiting the enzymatic activity of USP7 (P22077) has a drastic effect on ABC‐DLBCL, but not GCB‐DLBCL cells. Compared to GCB‐DLBCL, ABC‐DLBCL cells show transcriptional upregulation of multiple components of BCR‐signaling. USP7 inhibition significantly reduces the expression of upregulated components of BCR signaling. Mechanistically, USP7 inhibition greatly reduces the methylation of histone 3 on lysine 4 (H3K4me2), which is an epigenetic marker for active enhancers. USP7 inhibition greatly reduces the protein level of WDR5 and MLL2, key components of lysine‐specific methyltransferase complex (complex of proteins associated with Set1 [COMPASS]). In ABC‐DLBCL cells, USP7 stabilizes WDR5 and MLL2. In patients, the expression of USP7 is significantly associated with components of BCR signaling (LYN, SYK, BTK, PLCG2, PRKCB, MALT1, BCL10, and CARD11) and targets of BCR signaling (MYC and IRF4). In summary, we demonstrated an essential role of USP7 in ABC‐DLBCL by organizing an oncogenic epigenetic program via stabilization of WDR5 and MLL2. Targeting USP7 might be a novel and efficient approach to treat patients with ABC‐DLBCL and it might be better than targeting individual components such as BTK in BCR signaling. Abstract : Significance statement: The survival of activated B‐cell‐like (ABC)‐diffuse large B‐cell lymphoma (ABC‐DLBCL) relies on constitutive activation of BCR signaling. However, the underlying mechanism to induce constitutive activation of BCR‐NF‐κB signaling remains elusive. Here, we found ABC‐DLBCL show upregulation of multiple key components in BCR signaling to reduce the threshold for activation. Ubiquitin‐specific protease 7 (USP7) stabilizes the COMPASS (complex of proteins associated with Set1) complex to introduce an open chromatin state and subsequently upregulates all key components in BCR signaling. USP7 is an essential gene for ABC‐DLBCL survival and inhibition of USP7 promotes the death of DLBCL cells. Thus, USP7 is a druggable target for DLBCL and deserves to be tested in more clinically relevant models.